Crime, Justice and Human Rights - Weber, Leanne (Macmillan Education UK, 2014)
A specialized introduction to the philosophy, law and politics of human rights, uniquely tailored to criminologists and criminal justice practitioners. Exploring the connections between existing criminological scholarship and human rights frameworks, the book helps readers to incorporate human rights paradigms into their criminological analysis.